Breastfeeding initiation: An in-depth qualitative analysis of the perspectives of women and midwives using Social Cognitive Theory. (February 2018) - Edwards, M.E.; Jepson, R.G.; McInnes, R.J.
Abstract: Objective: to explore women's and midwives' expectations, knowledge and experiences of breastfeeding initiation using Social Cognitive Theory. Design: a qualitative study using focus group discussions and individual interviews. Breastfeeding initiation was defined for this study as a process within the first 48 hours after birth. Data were analysed using qualitative inductive analysis then further deductive analysis using Social Cognitive Theory (SCT). Setting and participants: a purposefully selected sample of primigravid antenatal and postnatal women (n=18) and practising midwives (n=18) from one Health Board area in Scotland. Findings: attachment of the baby to the breast at birth was hindered by sleepy babies and the busy unfamiliar hospital environment. These resulted in mothers struggling to maintain their motivation to breastfeed and to develop low self-efficacy. Instinctive attachment was rare. Midwives who considered it was normal for babies to be sleepy and unable to attach or feed at birth did not facilitate instinctive baby behaviour. Midwives sometimes experienced lack of autonomy and environmental circumstances that made women centred care difficult. Furthermore caring for high numbers of women, dependent on their help, resulted in reduced self-efficacy for providing effective breastfeeding support. Key conclusions: interviewing both women and midwives specifically about initiation of breastfeeding has allowed for deeper insights into this critical period and enabled a comparison between the data obtained from mothers and midwives. The findings suggest that instinctive attachment is not an expectation of either mothers or midwives and results in a loss of breastfeeding confidence in both. Implications for practice: to facilitate initiation there is a need for more research to develop appropriate maternal and midwifery skills, and make changes to the cultural environment in hospitals. Social Cognitive Theory could be used as a framework in both the antenatal and immediate postnatal period to develop strategies and materials to increase women's and midwives' self-efficacy specifically in initiation. Highlights: Low self-efficacy may be due to a mismatch between expectations and experiences. Women anticipated breastfeeding help from midwives but midwives anticipated problems. The baby's instinctive feeding behaviour was not expected to lead to breastfeeding.